DEVELOPING HOTS-BASED DESCRIPTIVE READING MATERIALS IN INDONESIAN CONTEXT FOR TENTH GRADERS - Irnansyah Irnansyah; Soni Mirizon; Ismail Petrus (English Review: Journal of English Education, 2022)
The objective of this study was to find out the validity, practicality, and potential effect of the developed HOTS-based descriptive texts in Indonesian context for senior high school students. In conducting this study Akker (1999) development concept consisting of analysis, design, evaluation, and revision was applied. The formative evaluation consisted of self-evaluation, expert review, one-to-one evaluation, small group evaluation, and field test adopted from Tessmer (1993) was used to see the validity, practicality, and the potential effect of the developed product. The result of the expert review showed that the average score of all aspects of the developed product was 3.71> 2.51, which means it was categorized as very high. Based on the practicality evaluation results in the one-to-one and small group evaluations, the product was highly practical since the average score in both phases was 2.9 and 3.07, respectively. The potential effect of the product was good enough (81%), although 4 out of 21 students in the field test could not reach the minimum mastery ≥70.